2020
DOI: 10.3847/1538-4365/ab9366
|View full text |Cite
|
Sign up to set email alerts
|

Microlensing Optical Depth and Event Rate in the OGLE-IV Galactic Plane Fields

Abstract: Searches for gravitational microlensing events are traditionally concentrated on the central regions of the Galactic bulge but many microlensing events are expected to occur in the Galactic plane, far from the Galactic Center. Owing to the difficulty in conducting high-cadence observations of the Galactic plane over its vast area, which are necessary for the detection of microlensing events, their global properties were hitherto unknown. Here, we present results of the first comprehensive search for microlensi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
57
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(64 citation statements)
references
References 48 publications
7
57
0
Order By: Relevance
“…The Gaia19bld event lies in the OGLE-IV disc field GD1298.15, and was already reported by Mróz et al (2020) in the comprehensive statistical study of 630 microlensing events found by the OGLE project in the Galactic disc. OGLE provides a fairly complete light curve, because the cadence for this field was increased for the duration of the event from one per week to one per day.…”
Section: Ogle Datasupporting
confidence: 57%
“…The Gaia19bld event lies in the OGLE-IV disc field GD1298.15, and was already reported by Mróz et al (2020) in the comprehensive statistical study of 630 microlensing events found by the OGLE project in the Galactic disc. OGLE provides a fairly complete light curve, because the cadence for this field was increased for the duration of the event from one per week to one per day.…”
Section: Ogle Datasupporting
confidence: 57%
“…This explains the sharp drop-off in long-duration events around this point. Mróz et al (2020a) conducted the largest Galactic plane search for microlensing events prior to this work, discovering 630 events in the OGLE survey observing 3000 square degrees of the Galactic plane between 2013 and 2019. ZTF Lam et al (2020) found that black holes could be identified by placing microlensing events in the t E -π E space and looking for the events with the largest t E and the shortest π E .…”
Section: Discussionmentioning
confidence: 99%
“…The Expérience pour la Recherche d'Objets Sombres (EROS) spiral arm surveys (Rahal et al 2009) observed 12.9 million stars across four directions in the Galactic plane and discovered 27 microlensing events over seven years between 1996 and 2002. The Optical Gravitational Lensing Experiment (OGLE; Mróz et al (2020a)) discovered 630 events in 3000 square degrees of Galactic plane fields in the 7 years between 2013 and 2019. They measured a threefold increase in the average Einstein crossing time for Galactic plane events as compared to the Galactic bulge and an asymmetric optical depth that they interpret as evidence of the Galactic warp.…”
mentioning
confidence: 99%
“…Such an effect, combined with a large timescale t E can be used to constrain the mass of the lens and to find microlensing dark remnants candidates (Poindexter et al 2005;Wyrzykowski et al 2016;Wyrzykowski & Mandel 2020;Lam et al 2020;Karolinski & Zhu 2020;Abrams & Takada 2020;Mróz & Wyrzykowski 2021). The longest ever detected microlensing event had a timescale of 640 +68 −54 days (Mao et al 2002) and only a few known events have timescales around 400 days (Wyrzykowski et al 2015;Mróz et al 2020). Terrestrial parallax occurs when a microlensing event is observed from two separate observatories on Earth.…”
Section: Introductionmentioning
confidence: 99%